Women's Resistance Against Gender Oppression in Dalcher's 'Vox' Seen from the Existential Feminism Lens - Shahnaz Amalia Putri; Sri Sumaryani (Universitas Islam Negeri Palopo, 2026)
This study analyzes Christina Dalcher’s Vox from an existential feminist perspective, describing how the female characters in the novel express their resistance to oppressive society through dialogue and statements to regain their identities and affirm their existence. Through the dystopian genre, this novel depicts a society in which women lose their voices, autonomy, and access to knowledge, resulting in a patriarchal system that controls their rights and roles. While previous studies have shown several analyses of this novel with different results, such as discrimination and the representation of the female body and gender to negotiate freedom, there are no in-depth analyses regarding how women resist the oppressive society through daily life actions from the perspective of existential feminism, which creates a gap in this field. Using a qualitative research method, this study analyzes expressions in the novel, classifying them into four types: the use of harsh expressions and profanity; dressing boldly and the use of the color red; creating an alternative communication medium; and acts of rebellion and protest. Each category comprises expressions that indicate resistance and defiance, asserting agency, which are later analyzed from the perspective of existential feminism, in terms of regaining freedom, transcending societal position, and rejecting the status of being ‘the Other.’ This strategy later reveals that their actions serve as a tool to reclaim their autonomy and regain their identity. By analysing Vox through an existential feminist perspective, this novel contributes to feminist literary study by highlighting how everyday activity and hidden resistance can become a form of agency, whilst expanding understanding of how women can regain their existence within an oppressive society.